2020
DOI: 10.3390/math8061043
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Natural Convection in a Concentric Hexagonal Annulus Using the Lattice Boltzmann Method Combined with the Smoothed Profile Method

Abstract: This research work presents results obtained from the simulation of natural convection inside a concentric hexagonal annulus by using the lattice Boltzmann method (LBM). The fluid flow (pressure and velocity fields) inside the annulus is evaluated by LBM and a finite difference method (FDM) is used to get the temperature filed. The isothermal and no-slip boundary conditions (BC) on the hexagonal edges are treated with a smooth profile method (SPM). At first, for validating the present simulation technique, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…For controlling fluid flow because of convection in an enclosure, the researchers are using the detached obstacle of varying shapescircular cylinder (Jami et al, 2007;Angeli et al, 2008;Raizah, 2017;Toghraie et al, 2019;Alsabery et al, 2019;Selimefendigil et al, 2019;Selimefendigil and Öztop, 2015;Selimefendigil and Öztop, 2018), square (Ha and Jung, 2000;Alsabery et al, 2020), triangular (Xu et al, 2009;Sheikholeslami et al, 2015), hexagonal (Gangawane and Manikandan, 2017;Alapati, 2020;El Moutaouakil et al, 2017), elliptical (Bararnia et al, 2011;Tayebi et al, 2019;Dogonchi et al, 2020), wavy shape (Hashemi-Tilehnoee et al, 2020), etc.which are needed for industrial applications. Md et al (2009) analyzed the numerical study of combined free and forced convection between a rectangular cavity and a heat-conducting circular cylinder.…”
Section: Subscripts F = Fluid;mentioning
confidence: 99%
See 1 more Smart Citation
“…For controlling fluid flow because of convection in an enclosure, the researchers are using the detached obstacle of varying shapescircular cylinder (Jami et al, 2007;Angeli et al, 2008;Raizah, 2017;Toghraie et al, 2019;Alsabery et al, 2019;Selimefendigil et al, 2019;Selimefendigil and Öztop, 2015;Selimefendigil and Öztop, 2018), square (Ha and Jung, 2000;Alsabery et al, 2020), triangular (Xu et al, 2009;Sheikholeslami et al, 2015), hexagonal (Gangawane and Manikandan, 2017;Alapati, 2020;El Moutaouakil et al, 2017), elliptical (Bararnia et al, 2011;Tayebi et al, 2019;Dogonchi et al, 2020), wavy shape (Hashemi-Tilehnoee et al, 2020), etc.which are needed for industrial applications. Md et al (2009) analyzed the numerical study of combined free and forced convection between a rectangular cavity and a heat-conducting circular cylinder.…”
Section: Subscripts F = Fluid;mentioning
confidence: 99%
“…Also, the presence of a rotating heat source and the direction of rotation affected remarkably the fluid flow and heat transfer. Alapati (2020) presented the simulation of natural convection inside a concentric hexagonal annulus by using the lattice Boltzmann method for evaluating the fluid flow (pressure and velocity fields), a finite difference method to get the temperature field and a smooth profile method to compute isothermal and no-slip boundary conditions (BC) on the hexagonal edges. The results showed that multiple circulation zones and distorted isotherms were observed at the high Ra because of the strong convective flow.…”
Section: Subscripts F = Fluid;mentioning
confidence: 99%
“…Heat convection investigated for a range of Rayleigh number and different volume fractions for nano-fluid [1]. The noncircular geometry of the internal pipe (rather than circular like square, elliptical, triangular, and hexagonal) attracts the attention also and many investigations have been done on different shapes of the internal pipe rather than circular shape [2,3]. In addition, several boundary conditions for annular spaces have been conducted such as partial heated internal duct [4].…”
Section: Introductionmentioning
confidence: 99%
“…Seyyedi et al (2020) examined the influences of a magnetic field on entropy generation and natural convection of Cu-H 2 O nano-liquid inside a hexagonal cavity. Alapati (2020) used the lattice Boltzmann method to simulate the natural convection in a concentric hexagonal annulus. Hosseinzadeh et al (2021a, 2021b, 2021c) simulated the heat and flow inside an octagon cavity having an elliptical blocked filled with hybrid nanofluid with water–ethylene glycol contains MoS 2 –TiO 2 hybrid nanoparticles by using the FEM.…”
Section: Introductionmentioning
confidence: 99%